2022
DOI: 10.1123/ijspp.2021-0334
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Rating of Perceived Exertion Growth During Fatiguing Tasks is Scalar and Independent of Exercise Mode

Abstract: Introduction: The relationship between the percentage of a fatiguing ambulatory task completed and rating of perceived exertion (RPE) appears to be linear and scalar, with a relatively narrow “window.” Recent evidence has suggested that a similar relationship may exist for muscularly demanding tasks. Methods: To determine whether muscularly demanding tasks fit within this “ambulatory window,” we tested resistance-trained athletes performing bench press and leg press with different loadings predicted to allow 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…Several studies have shown that RPE grows in a systematic manner in relation to the percentage of a task completed. 25,28,29,[79][80][81][82][83][84][85][86][87][88][89] This suggests a scaling of RPE to the overall level of homeostatic disturbance, regardless of the precise nature of the disturbance. The rate of RPE growth during an event appears to be tightly regulated, as blinded changes in inspired (O 2 ) cause a rapid change in muscular power output while the rate of RPE growth barely changes.…”
Section: Rating Of Perceived Exertionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that RPE grows in a systematic manner in relation to the percentage of a task completed. 25,28,29,[79][80][81][82][83][84][85][86][87][88][89] This suggests a scaling of RPE to the overall level of homeostatic disturbance, regardless of the precise nature of the disturbance. The rate of RPE growth during an event appears to be tightly regulated, as blinded changes in inspired (O 2 ) cause a rapid change in muscular power output while the rate of RPE growth barely changes.…”
Section: Rating Of Perceived Exertionmentioning
confidence: 99%
“…Data included are for ambulatory tasks such as walking, running, and cycling, as well as for lifting weights to failure with different levels of resistance. 21,25,28,51,53,54,64,72,80,88,[93][94][95][96] Hazard score (momentary RPE × fractional distance remaining), which seems to be able to inform athletes when to change power output during an event. 82,84,95,96 An extension of this technique, the summated Hazard score, has been shown to allow appreciation of how taxing an event feels.…”
Section: Rating Of Perceived Exertionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Meyer et al. (2022), the authors found that the perception of effort increases in a scalar manner relative to the percentage of maximal subject capacity in a physical task (i.e., the maximum number of repetitions or total distance), which means that mental fatigue might have a negative effect independently of the physical task performed. It corroborates recent findings of dynamic resistance exercises that show a reduction in the number of repetitions performed to failure in mentally fatigued individuals (Gantois et al., 2021; Queiros et al., 2021).…”
Section: Introductionmentioning
confidence: 99%